Effect of surgical release of entrapped peripheral nerves in sensorimotor diabetic neuropathy on pain and sensory dysfunction: study protocol of a prospective, controlled clinical trial - Däschler, Simeon C.; Pennekamp, Anna; Tsilingiris, Dimitrios; Bursacovschi, Catalina; Amann, Martin; Eisa, Amr; Böcker, Arne Hendrik; Klimitz, Felix; Stolle, Annette M.; Kopf, Stefan; Schwarz, Daniel; Bendszus, Martin; et al. (Journal of Personalized Medicine, 2023)
Background: Nerve entrapment has been hypothesized to contribute to the multicausal etiology of axonopathy in sensorimotor diabetic neuropathy. Targeted surgical decompression reduces external strain on the affected nerve and, therefore, may alleviate symptoms, including pain and sensory dysfunction. However, its therapeutic value in this cohort remains unclear. Aim: Quantifying the treatment effect of targeted lower extremity nerve decompression in patients with preexisting painful sensorimotor diabetic neuropathy and nerve entrapment on pain intensity, sensory function, motor function, and neural signal conduction. Study design: This prospective, controlled trial studies 40 patients suffering from bilateral therapy-refractory, painful (n = 20, visual analogue scale, VAS ≥ 5) or painless (n = 20, VAS = 0) sensorimotor diabetic neuropathy with clinical and/or radiologic signs of focal lower extremity nerve compression who underwent unilateral surgical nerve decompression of the common peroneal and the tibial nerve. Tissue biopsies will be analyzed to explore perineural tissue remodeling in correlation with intraoperatively measured nerve compression pressure. Effect size on symptoms including pain intensity, light touch threshold, static and moving two-point discrimination, target muscle force, and nerve conduction velocity will be quantified 3, 6, and 12 months postoperatively, and compared (1) to the preoperative values and (2) to the contralateral lower extremity that continues non-operative management. Clinical significance: Targeted surgical release may alleviate mechanical strain on entrapped lower extremity nerves and thereby potentially improve pain and sensory dysfunction in a subset of patients suffering from diabetic neuropathy. This trial aims to shed light on these patients that potentially benefit from screening for lower extremity nerve entrapment, as typical symptoms of entrapment might be erroneously attributed to neuropathy only, thereby preventing adequate treatment.
Gesehen am 01.10.2025